KEPEMIMPINAN NON MUSLIM DI INDONESIA PERSPEKTIF HUKUM ISLAM - Muhammad Jufri; Ahmad Dahlan (LP2M Universitas Ibrahimy, 2018)
There is a difference of opinion related to the non-muslim skill of being a leader. Differences are: The first is not allowed, the second may be in the realm of the executive only, and also the third may be conditional. For Muslims chosen non Muslim as the leader of the law is the same with non-Muslim law becomes the leader.